Observation of a low Curie temperature ferromagnetic phase of ultrathin epitaxial Fe films on GaAs(0 0 1) - Spangenberg, M.; Neal, J.R.; Shen, T.-H.; Morton, S.A.; Tobin, J.G.; Waddill, G.D.; Matthew, J.A.D.; Greig, D.; Malins, A.E.R.; Seddon, E.A.; Hopkinson, M. (Journal of magnetism and magnetic materials, 2005)
The magnetic properties of epitaxial Fe films on GaAs in the range of the first few monolayers have been the subject of a considerable number of investigations in recent years. The absence of magnetic signatures at room temperature has been attributed to the existence of a magnetic ‘dead’ layer as well as superparamagnetism. By examining the temperature dependence of the magnetic linear dichroism of the Fe core level photoelectrons, we found a ferromagnetic regime with a Curie temperature, T c substantially lower than room temperature, e.g., a T c of about 240 K for thin films of a nominal thickness of 0.9 nm. The values of Curie temperature were sensitive to the initial GaAs substrate conditions and the thickness of the Fe over-layer with a layer of thickness of 1.25 nm showing a T c above room temperature. The data suggest that the thin Fe films on GaAs(0 0 1) may have ferromagnetic character at an earlier stage of growth than previously expected, although a weaker exchange interaction in the films leads to a substantial reduction in Curie temperature.